Understanding Cyber-Racism Perpetration within the Broader Context of Cyberbullying Theory: A Theoretical Integration - Jordan E. Scott; Christopher P. Barlett (MDPI AG, 2023)
The purpose of the current theoretical review is to argue for the theoretical integration of cyber-racism perpetration into the broader cyberbullying context-making note of the similarities between both types of nefarious online behavior that make this integration appropriate and the differences that make the integration less clear. Cyber-racism and cyberbullying victimization have been shown to be prevalent in youth and is related to poor psychological outcomes. Understanding both types of antisocial online behaviors have implications for the understanding and subsequent reduction of cyber-racism. Our review focuses on a cyber-racism model that proposes the importance of anonymity perceptions afforded to the online user to cause cyber-racism via several routes that focus on (a) online disinhibition, (b) deindividuation and group polarization, and (c) stereotypes. We discuss the tenets of this theory and the overlap with the Barlett Gentile Cyberbullying Model-a learning-based model that focuses on how anonymity eventually predicts cyberbullying via the development of positive cyberbullying attitudes. We believe that theoretical integration is necessary; however, future work needs to test several theoretical underpinnings of these models first. We end with a discussion of theoretical and intervention implications before discussing limitations and future work. Overall, we hope this review sparks interesting future research to understand cyber-racism and broaden the existing research on cyberbullying.